Different friction pairs of hip prostheses - Filipenko, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The authors describe the evolution of friction pairs of hip prostheses, point out advantages and shortcomings of each of them. Modern friction pairs, which ensure the best long-term results, are singled out.